SMALLSOA – Um Motor para Execução de Composições de Serviços em Ambientes Móveis - Zanuz, Luciano (Universidade do Vale do Rio do Sinos, 2009)
Services-oriented architectures (SOA) restarted to gain prominence after the emergence of web services as a technology able to improve the interoperability between software applications. To support the growing need for collaboration between people physically separated as in distance work or learning systems, collaborative environments are being constructed using the Internet as platform. With the popularization of mobile devices, software that allows interactions between any devices, mobile or not, using different communication technologies towards a ubiquitous world are gaining prominence. SOA, in its turn, is considered one of the most suitable platforms for ubiquitous collaborative systems. This work presents SmallSOA, an engine for services compositions execution on mobile environments, one of the central components of the service oriented architecture called U-SOA that the research team on Software Engineering and Programming Languages at Unisinos is developing. An engine for services compositions exec
Keywords: Android; computação móvel; computação ubíqua; motor de execução; SOA; execution engine; mobile computing; ubiquitous computing; web services; Ciências Exatas e da Terra